Fracture Characteristics of Titanium VT1-0 and Zr-1 wt. % Nb Alloy in Different Structures under Gigacycle Fatigue Loading Regime; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Mairambekova A.; Eroshenko А.; Bannikov M.; Naimark O.; Sharkeev Yu. P. Yury Petrovich (2018, 2018)
Title screen